New data on the age of the Lower Cretaceous amber outcrops of Lebanon - Maksoud, Sibelle; Azar, Dany; Granier, Bruno; Gèze, Raymond (Palaeoworld, 2017)
The “Grès du Liban” [Sandstone of Lebanon] is the basal lithostratigraphic unit for the Cretaceous series in Lebanon. In the upper part of these siliciclastic-dominated strata we identified three discrete intervals characterized by their richness in amber with biological inclusions, mostly insects. The middle and upper intervals previously attributed to an Early Aptian (= Bedoulian) age are nowadays ascribed to the Early and Late Barremian respectively; the lower interval is Early Barremian or possibly older. Besides that it is suggested that pieces of amber with inclusions from the middle and upper intervals could be reworked from the lower interval. In conclusion, the new dating of arthropod-bearing localities allows us to push back in time (at least to the Early Barremian) the first occurrences of all biological inclusions found therein.